Diagnosing Angola’s WASH Sector : An Urgent Call to Action - Lombana Cordoba, Camilo; Andres, Luis A.; Da Costa, Lucrecio A.M.; Fenwick, Crystal (World Bank, Washington, DC, 2021)
Angola’s human development potential is constrained by the state of its water supply, sanitation, and hygiene (WASH) sector. The Angola WASH sector diagnostic identifies key service-delivery problems in the WASH sector and their enabling environment through an institutional assessment and political economy analysis that takes into account the cross-sectoral links underpinning human development. Specifically, the diagnostic first explores inequalities in access to WASH services and their relationship to childhood health in Angola, using data from the most recent demographic health survey (DHS, 2015-16) and the joint monitoring program (JMP) of the United Nations Children’s Fund and World Health Organization. Next, the diagnostic identifies key institutional constraints and bottlenecks through a comprehensive governance and public expenditure review of Angola’s WASH sector. Finally, the report provides guidance on how to improve the effectiveness of the WASH sector in support of broader policy goals to achieve sustainability and meet the targets of the sustainable development goals (SDGs). The diagnostic answers the following questions, each of which probes the links between access to safe WASH services and human development and highlights opportunities to improve policy, investments, and practice: (1) what is the current level and quality of access to WASH services in Angola, and how does access vary temporally and spatially?; (2) what are the links and synergies between WASH and other sectors critical to human development in Angola?; (3) what constrains WASH service delivery; and (4) what solutions will have the greatest effect on overall human development?